2013
DOI: 10.1089/acm.2012.0058
|View full text |Cite
|
Sign up to set email alerts
|

Open-Label, Randomized, Parallel-Group Controlled Clinical Trial of Massage for Treatment of Depression in HIV-Infected Subjects

Abstract: Objectives: The study objectives were to determine whether massage therapy reduces symptoms of depression in subjects with human immunodeficiency virus (HIV) disease. Design: Subjects were randomized non-blinded into one of three parallel groups to receive Swedish massage or to one of two control groups, touch or no intervention for eight weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This may indicate that suicidal patients who did not receive the contact intervention needed to obtain this contact in a physical way (in addition to obtaining pain relief). In a randomized controlled trial, 47 Poland et al. found that Swedish massage significantly reduced the severity of depression at weeks 4, 6 and 8 compared with no intervention and/or touch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may indicate that suicidal patients who did not receive the contact intervention needed to obtain this contact in a physical way (in addition to obtaining pain relief). In a randomized controlled trial, 47 Poland et al. found that Swedish massage significantly reduced the severity of depression at weeks 4, 6 and 8 compared with no intervention and/or touch.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that suicidal patients who did not receive the contact intervention needed to obtain this contact in a physical way (in addition to obtaining pain relief). In a randomized controlled trial, 47 Poland et al found that Swedish massage significantly reduced the severity of depression at weeks 4, 6 and 8 compared with no intervention and/or touch. This suggests that massage without monoı¨and ylang ylang oils may also be effective for suicidal behaviour, but this effect remains to be tested (Poland et al did not examine suicidal behaviour).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on HIV adults with a major depressive disorder, one group received Swedish massage and the second group received touch alone [64]. The massage was received for one hour twice per week.…”
Section: Immune Disorders (See Table 5)mentioning
confidence: 99%
“…Numerous studies found that measures of anxiety and depression were signif icantly improved following massage therapy. (62)(63)(64) One proposed pathway for the devel- opment of anxiety and depressive symptoms in Long COVID Syndrome patients is elevated levels of inflammatory cytokines, specifically interleukin-6 (IL-6) and tumor necrosis factor-a (TNF-a). (65) Massage therapy decreases both IL-6 and TNF-a levels; (66) thus, it has the potential to be an effective treatment for this mechanism of neuropsychiatric symptom development.…”
Section: Massage Therapy Treatment Of Long Covid Syndrome Sequelae An...mentioning
confidence: 99%